Associated factors of depression in pregnant women in Korea based on the 2019 Korean Community Health Survey: a cross-sectional study - Eun Gyeong Kim; Sook Kyoung Park; Ju-Hee Nho (Korean Society of Women Health Nursing, 2022)
Purpose Various individual and social factors influence depression in pregnant women. The purpose of this study was to identify the influence of socioeconomic status, health behaviors, and health status on depression of pregnant women in Korea. Methods This study analyzed data from the 2019 Korean Community Health Survey conducted from August to October 2019. A structural questionnaire with Patient Health Quetsionnaire-9 (PHQ-9), health behavior, health status, and psychological characteristics was used. The data of 1,096 pregnant women between the ages of 19 and 55 years were analyzed using descriptive statistics, independent-test and chi-square tests, and multiple regression. Results The mean score of prenatal depression as measured by the PHQ-9 during pregnancy was 2.35 points out of 0 to 27 points. Low income (B=0.69, p<.001), low-education level (B=0.70, p<.001), skipping breakfast (B=0.34, p=.001), less than 8 hours of sleeping (B=0.26, p=.009), binge drinking during pregnancy (B=0.46, p=.001), and stress (B=1.89, p<.001) were significantly associated with increased depression scores. In contrast, depression scores significantly decreased as subjective health status (B=-0.59, p<.001) and subjective oral health status (B=-.17, p=.003) increased. Conclusion Findings support the need for healthcare policies and clinical screening to alleviate prenatal depression, especially for pregnant women with low socioeconomic status, poor health behavior, poor health status, and high stress.